The Normative Vacuum in Notarial Criminal Liability for Negligence in Preparing Authentic Deeds Used in Money Laundering Crimes - Brighitta Priscilla MSS; Wilma Silalahi (Journal of Law, Politic and Humanities, 2026)
This study examines the limits of notarial criminal liability in the preparation of authentic deeds used in money laundering offences. The issue arises because notaries are authorized to draw up authentic deeds with strong evidentiary value, while such deeds may also be misused to conceal or disguise assets derived from criminal activities. This research applies normative legal research using statute and case approaches. The findings show that a notary cannot be held criminally liable merely because an authentic deed is later used in a money laundering scheme. Criminal liability may only arise when fault is proven, whether in the form of intent, knowledge, reasonable suspicion, or serious negligence. Court decisions indicate that judges tend to interpret negligence and “reasonably suspects” through an objective-professional standard. However, Indonesian positive law has not clearly distinguished administrative negligence, gross professional negligence, and criminal participation. This normative vacuum creates legal uncertainty and may lead to the criminalization of notaries who perform their duties in good faith.